A Study On The Use Of Blackboard In The Analysis Of The Use Of The Learning Management System (Lms) - Pratama Dahlian Persadha; Loso Judijanto; Melly Susanti; Dian Permatasari Kusuma Dayu (Departement of Mathematics Education, 2024)
I Learning Management Systems (LMS), which have expedited the transition from in-person instruction to online learning, are the only foundational component of the learning system. This study aims to examine lecturers' views about social interaction, output, e-learning framework, and e-learning. LSM-using lecturers made up the sample. Data were gathered using a semi-structured interview instrument, and analysis was performed using the objective analysis approach. The results imply that professors can benefit from using Blackboard to help with distance learning. This distance learning can be enhanced by using synergy between electronic and traditional systems and by continuing to learn through electronic platforms.